Penyebaran Jenis Jirak (Symplocos fasciculata Zoll.) di Resort Kawah Ratu Taman Nasional Gunung Halimun Salak, Jawa Barat - Iwan Hilwan; Aldi Perdana Wiraatmadja (Jurnal Silvikultur Tropika, 2021)
Jirak (Symplocos fasciculata Zoll.) is one of the native species in the Gunung Halimun Salak National Park, especially in the Kawah Ratu resort. This plant can be used as a natural coloring agent, in addition to plant parts such as leaves can also be eaten and used as medicine. Because of the benefits of jirak, this plant is considered important to be cultivated. This study aims to analyze the density and distribution pattern of jirak (Symplocos fasciculata Zoll.) at Kawah Ratu Resort, Gunung Halimun Salak National Park. Data collection was carried out in two blocks located at the Kawah Ratu Resort of Mount Halimun Salak National Park, namely the Leles block and the Pamengpeuk block using the single plot method. The results showed that jirak distribution pattern in the two observation blocks was grouped. Keywords: Distribution, Jirak, Kawah Ratu Resort, Symplocos fasciculata Zoll., Gunung Halimun Salak National Park